ANALYSIS OF FINANCIAL REPORTS TO ASSESS FINANCIAL PERFORMANCE - Yuniawati, Ayi Srie; Farman, Fanji (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The purpose of establishing a company in general is to maximize profits, increase sales, maximize share value, and increase the welfare of shareholders. This can be seen in reports, reports that explain the development of a company's financial performance over a certain period. These reports are usually referred to as financial reports. For financial reports to be meaningful to interested parties, it is necessary to analyze the relationship of each item in the financial statements, which is often referred to as financial statement analysis. This research was conducted to find out how the financial performance of PT. Jasa Marga Tbk is based on the ratio analysis of profitability, liquidity, and solvency. The data analysis method used is a quantitative descriptive method using profitability, liquidity, and solvency ratios. Based on the research results of the three ratios, it can be concluded that the financial performance of PT. Jasa Marga Tbk from 2017-2021 as a whole experienced conditions that tended to decline, this showed that the company's financial performance was in unfavorable condition.